Euro area business confidence and Covid-19 - Gene Ambrocio (Bank of Finland, 2021)
I study the effects of the Covid-19 pandemic on business confidence in 11 Euro area countries and its consequent impact on economic activity. To obtain causal effects, I instrument business confidence with domestic household confidence as well as average household confidence in neighboring countries. I find evidence suggesting that the confidence and expectations channel was an important component to the economic transmission of Covid-19. A one standard deviation drop in business confidence leads to between 5-6 and 9 percent fall in economic activity in the industrial and wholesale and retail trade sectors respectively. These results highlight the importance of managing confidence and expectations in crises episodes.
URN:NBN:fi:bof-202103121132
Keywords: E23; E66; E71; I12; 330; Business confidence; survey expectations; Covid-19